1995
DOI: 10.1116/1.579668
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur layer formation on GaAs(100) by thermal and photochemical H2S dissociation

Abstract: We have studied the formation of sulfide layers on the GaAs͑100͒ c(8ϫ2) gallium rich surface through thermal and photoinduced ͑193 nm͒ decomposition of H 2 S. H 2 S was adsorbed on the sample at 90-95 K. The sulfide layer desorbs as Ga 2 S beginning at 740 K. For thermal sulfide layer formation, it was found that more sulfur could be built up on the surface by repeated cycles of H 2 S exposure at low temperature followed by heating to 600 K. Several such cycles gave a sulfide layer saturating at about one mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…23,24 In addition, phosphorus hydrides (PH and PH 2 ) may decompose at high temperatures and the resulting H atoms may desorb from the surface in the form of molecular H 2 or react with neighboring HS on the In atom to cause a recombinative desorption of H 2 S (b). 34,35 The chemisorbed sulfur species may desorb at elevated temperatures. As shown in Figure 6, the In 4d intensity on the high binding energy side decreases with an increase of the sample temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 In addition, phosphorus hydrides (PH and PH 2 ) may decompose at high temperatures and the resulting H atoms may desorb from the surface in the form of molecular H 2 or react with neighboring HS on the In atom to cause a recombinative desorption of H 2 S (b). 34,35 The chemisorbed sulfur species may desorb at elevated temperatures. As shown in Figure 6, the In 4d intensity on the high binding energy side decreases with an increase of the sample temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The gradual loss of P was thought to be replaced with S to form the InS compound of one monolayer. It was also demonstrated that hydrogen can preferentially etch phosphorus atoms from the InP surface to form an In-rich surface with the presence of In clusters. , In addition, phosphorus hydrides (PH and PH 2 ) may decompose at high temperatures and the resulting H atoms may desorb from the surface in the form of molecular H 2 or react with neighboring HS on the In atom to cause a recombinative desorption of H 2 S (b). ,
4 Soft X-ray photoelectron spectra of S 2p, collected from the InP surface exposed to 3.0 L of H 2 S at 100 K followed by annealing the sample to the indicated temperatures.
5 Soft X-ray photoelectron spectra of P 2p from the InP(100) surface exposed to 3.0 L of H 2 S at 100 K followed by annealing the sample to the indicated temperatures.
…”
Section: Resultsmentioning
confidence: 99%
“…To get a rough estimate of the overlayer thickness we analyzed the overlayer/substrate intensities in XPS spectra, using the exponential attenuation of the substrate signal: , where d ol is the overlayer thickness, λ ol the corresponding electron mean free path, θ the electron take-off angle, relative to the plane of the surface, I sub ( d ol ) the substrate intensity in presence of the overlayer, and I sub (0) the substrate intensity when no overlayer is present. This analysis assumes that all of the material screens electrons equally, depending only on the overlayer thickness.…”
Section: Methodsmentioning
confidence: 99%
“…However, with all these advantages, GaAs has a serious problem: it suffers from a surface effect known as Fermi-level pinning. Extensive work dealing with the passivation of GaAs surfaces has been carried out. Sandroff et. al.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that using H 2 S gives a treated surface that is more stable in air or water . Recently the passivation of the GaAs surface involving gas phase sulfur compounds has attracted considerable attention. , As part of our attempt to passivate GaAs by gas phase sulfur deposition, the photochemistry of adsorbed OCS on GaAs has been studied.…”
Section: Introductionmentioning
confidence: 99%